Introduction to programming with C++ - Liang, Y. Daniel (Pearson/Prentice Hall, 2010)
This edition is available with MyProgrammingLab, an innovative online homework and assessment tool. Through the power of practice and immediate personalized feedback, MyProgrammingLab helps students fully grasp the logic, semantics, and syntax of programming